1977
DOI: 10.1021/j100534a017
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of the recombination fluorescence of photoionized indole and N,N,N',N'-tetramethyl-p-phenylenediamine in organic glasses. Consequences of electron tunneling and diffusion

Abstract: The recombination fluorescence seen when TMPD is photoionized in methylcyclohexane, 3-methylhexane, and 2-methyltetrahydrofuran glasses and when indole is photoionized in 2-propanol and ethanol glasses has been investigated. The initial intensity and decay rate of the recombination fluorescence decreases as the UV irradiation temperature is increased from temperatures below the glass transition temperature T% of the matrix. This is interpreted in terms of electron tunneling to the cation in which the tunneling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1980
1980
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…The time dependence of the delayed isothermal recombination luminescence of squalane glass was studied with TMPD replaced with 10 -4 M perylene. Following a single intense 308 nm laser pulse at 77 K, the luminescence was found to follow a t - a dependence with a = 1.05 over a time interval ranging from t = 100−10000 s. Such power law dependence has been previously observed in similar systems , and attributed to tunneling of a trapped electron to its sibling cation, with an exponential distribution of initial electron cation separation distances. In this case, a-1, has the simple interpretation as the ratio of the distance parameter in an assumed exponential form for the tunneling probability, to the average initial separation distance of the geminate pair.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…The time dependence of the delayed isothermal recombination luminescence of squalane glass was studied with TMPD replaced with 10 -4 M perylene. Following a single intense 308 nm laser pulse at 77 K, the luminescence was found to follow a t - a dependence with a = 1.05 over a time interval ranging from t = 100−10000 s. Such power law dependence has been previously observed in similar systems , and attributed to tunneling of a trapped electron to its sibling cation, with an exponential distribution of initial electron cation separation distances. In this case, a-1, has the simple interpretation as the ratio of the distance parameter in an assumed exponential form for the tunneling probability, to the average initial separation distance of the geminate pair.…”
Section: Resultssupporting
confidence: 59%
“…Low energy electrons produced by ionization can become trapped in nonpolar glasses. The physical properties of trapped electrons reflect the excess electron−solvent interactions that are of fundamental and practical interest regarding ionization in amorphous condensed phases. A number of experimental methods have been applied to elucidate the properties of electrons trapped in nonpolar glasses, including absorption spectroscopy, photoconductivity, , various forms of magnetic resonance, ,,, isothermal recombination luminescence, and the effects of electron scavengers. ,,,, Complementary to these methods is the technique of thermoluminescence, to which we confine our focus.…”
Section: Introductionmentioning
confidence: 99%
“…Ho, Moan and Kevan [12][13][14] suggested that the RL of indole derivatives and tetramethyl-pphenylenediamine was caused by the electron tunneling from traps to mother cations in aqueous or organic glasses.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, tunneling recombination of a trapped electron with the parent cation in organic glassy matrices has been followed through optical emission spectroscopy of the recombination center. Depending on the trap depth, either fluorescence or phosphorescence is observed; see Figure 14c [53].…”
Section: Charge Trapping/de-trappingmentioning
confidence: 99%